2010
DOI: 10.1029/2009jb006295
|View full text |Cite
|
Sign up to set email alerts
|

Tectonomagmatic activity and ice dynamics in the Bransfield Strait back‐arc basin, Antarctica

Abstract: [1] An array of moored hydrophones was used to monitor the spatiotemporal distribution of small-to moderate-sized earthquakes and ice-generated sounds within the Bransfield Strait, Antarctica. During a 2 year period, a total of 3900 earthquakes, 5925 icequakes and numerous ice tremor events were located throughout the region. The seismic activity included eight space-time earthquake clusters, positioned along the central neovolcanic rift zone of the young Bransfield back-arc basin. These sequences of small mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 40 publications
0
56
1
Order By: Relevance
“…In the past decades, a few detailed studies have revealed a significant background of low-magnitude microseismicity around the Bransfield rift (Dziak et al, 2010;Ibáñez et al, 1997;Pelayo & Wiens, 1989;Robertson-Maurice et al, 2003). Despite the poor permanent station coverage, the International Seismological Center (ISC) catalog (ISC, 2017) comprises ∼200 earthquakes with magnitudes above ∼4.0 since 1960.…”
Section: The 2014-2015 Livingston Seismic Swarmmentioning
confidence: 99%
“…In the past decades, a few detailed studies have revealed a significant background of low-magnitude microseismicity around the Bransfield rift (Dziak et al, 2010;Ibáñez et al, 1997;Pelayo & Wiens, 1989;Robertson-Maurice et al, 2003). Despite the poor permanent station coverage, the International Seismological Center (ISC) catalog (ISC, 2017) comprises ∼200 earthquakes with magnitudes above ∼4.0 since 1960.…”
Section: The 2014-2015 Livingston Seismic Swarmmentioning
confidence: 99%
“…Similar cryoseismic phenomena have also been reported around the Ross Sea region (MacAyeal et al, 2009), the marginal sea of the Antarctic Peninsula [33], as well as the continental margin of Dronning Maud Land [17]. In particular, iceberg-originated harmonic tremor emanating from tabular icebergs was observed by both seismo-acoustic and local broadband seismic signals [35].…”
Section: Ice-quakes Glacial Earthquakesmentioning
confidence: 51%
“…The so-called "ice-micity" detected around the Bransfield Strait and Drake Passage by a local network of hydrophone arrays in 2006-2007 illustrate the dynamic behavior of sea ice in the Bransfield and Antarctic Peninsula regions [33].…”
Section: Ice-quakes Glacial Earthquakesmentioning
confidence: 99%
“…Seismic signals involving ice-related phenomena are called 'ice-quakes' (ice-shocks for smaller ones), and are most frequently reported in association with glacier-related mass movements of ice sheets, or with sea-ice, tide-cracks and icebergs (Anandakrishnan & Alley 1997;Kanao & Kaminuma 2006;Wiens 2007;Nettles & Ekström 2010). The so-called 'ice-micity' detected around the Bransfield Strait and Drake Passage by a local network of hydrophone arrays in 2006-2007 illustrated the dynamic behaviour of sea-ice in the Antarctic Peninsula (Dziak et al 2009). Local seismicity around the Lützow-Holm Bay was reported by Kanao & Kaminuma (2006), who detected 17 events using a local network deployed around the Bay.…”
Section: Cryosphere Wave Signalsmentioning
confidence: 99%
“…7) and the Pan-Antarctic Observations System under the Scientific Committee on Antarctic Research. Hydroacoustic observations contribute to the understanding of wave-propagation inside the ocean, and have already been exploited to investigate seismicity and sea-ice dynamics around the Bransfield Strait, Antarctic Peninsula (Dziak et al 2009). The combination of seismic, infrasound and hydroacoustic observations is most likely required to understand in more detail the atmosphere -oceancryosphere-solid earth system and its variations with time.…”
Section: The Place Of Antarctica In the Global Networkmentioning
confidence: 99%